ON THE USE OF CHANGES IN DIHEDRAL ANGLE TO DECODE LATE-STAGE TEXTURAL EVOLUTION IN CUMULATES - Holness M.B.; Cheadle M.J.; McKenzie D. (My University, 2005)
The melt-filled pore structure in the final stages of solidification of cumulates must lie somewhere between the two end-members of impingement (in which pore topology is controlled entirely by the juxtaposition of growth faces of adjacent grains) and textural equilibrium (in which pore topology is controlled by the minimization of internal energies). The exact position between these two end-members is controlled by the relative rates of crystal growth and textural equilibration. For samples in which growth has stopped, or is very slow, textural equilibrium will prevail. A close examination of dihedral angles in natural examples demonstrates that these two end-member textures can be distinguished. The impingement end-member results in a population of apparent solid–melt dihedral angles with a median of ?60° and a standard deviation of ?25–30°, whereas the texturally equilibrated end-member population has a median of ?28° and a standard deviation of ?14°. For the specific case of cumulates in the Rum Layered Intrusion, residual porosity in troctolitic cumulates was close to the impingement end-member, whereas that in peridotites was close to melt-bearing textural equilibrium. Suites of glass-bearing samples from small, or frequently disturbed, magma systems show modification of initial impingement textures. These modifications may be a consequence of textural equilibration or of diffusion-limited growth during quenching. Distinction can be made between these two processes by a consideration of grain shape. The geometry of interstitial phases in suites of fully solidified cumulates from the Rum Layered Intrusion shows variable approach to sub-solidus textural equilibrium from an initial state inherited by pseudmorphing of the last melt. Textural equilibration at pore corners occurs as a continuous process, with a gradual movement of the entire dihedral angle population towards the equilibrium final state. If the initial, pseudomorphed state is one of disequilibrium (i.e. a melt-present impingement texture) this change is accompanied by a reduction in the spread of the population. If it is one of equilibrium, the change is accompanied by an initial increase in the spread of the population, followed by a decrease. These observations demonstrate that previously published models of dihedral angle change involving the instantaneous establishment of the equilibrium angle in the immediate vicinity of the pore corner are incorrect.